Labor and Capital Dynamics under Financing Frictions*. (3rd July 2018) - Michaels, Ryan; Beau Page, T; Whited, Toni M
Abstract: We assemble a new, quarterly panel dataset that links firms' investment and financing to their employment and wages. In the data, wages and leverage are negatively related, both cross-sectionally and within firms. This pattern contradicts models in which firms insure workers against unemployment risk. We reconcile this fact with a model that integrates factor adjustment frictions and wage bargaining with costly external financing. In the model, the probability of default rises with debt. Because default incurs deadweight costs, the expected surplus over which firms and workers bargain falls, thus depressing wages. We show that raising financing costs reduces employment and wages, in line with recent reduced-form evidence.